IMAGE FORMATION SCIENCE THE STUDENTS BY MEANS OF RESEARCH ACTIVITIES - Irina Peretrukhina (Вестник Северо-Кавказского федерального университета)
The article presents theoretical substantiation of the problem of forming the image of science undergraduates on the basis of reflection of pedagogical, psychological, sociological and other concepts in science. The possibilities ofthe formation ofthe image of science in the educational process of higher educational institutions by means of research activities is described by its organizational forms, types, functions and requirements. The necessity of integration of science and professional activity of a student. Given the promising research directions in the field of image science.